A desaprendizagem na prática docente: um estudo em cursos de mestrado profissional na área de Administração - Silva, Murilo Gabriel da Costa (2023)
Teaching practice involves constant transformations, influenced by factors such as education, identity, institutional rules and processes, participation of different agents, teaching strategies, as well as technological and social changes. These transformations require the acquisition of new knowledge, routines, technologies, tools, practices, customs, beliefs, and values, as well as the abandonment of some when deemed obsolete, leading to a process of redefinition, or unlearning. In this context, the general objective of this research is to understand the unlearning process in teaching practice, specifically in professional master's degree courses (CMPs) in the field of Administration in the northeastern region of Brazil. To achieve this purpose, the following specific objectives were established: (i) Investigate teaching practice in postgraduate education, specifically in professional master's degree courses; (ii) Analyze the transformations experienced by CMP professors in their teaching practice; (iii) Characterize the process and constitutive elements of unlearning by CMP professors; and (iv) Identify links between unlearning and teaching practice. For this, a qualitative approach was adopted, with data collection through interviews with semi-structured scripts, conducted with CMP professors in the northeastern region of Brazil. Data analysis followed the steps of interpretative comprehensive analysis. The results highlight the specificities of teaching practice in professional master's degree courses, emphasizing the challenges faced by professors in this context, including the theory-practice dilemma and the need for flexibility in the face of the singularities of these courses, as well as the Covid-19 pandemic, which has intensified the adoption of digital technologies and active teaching strategies, reflecting the continuous pursuit of improvement by teachers. Additionally, challenges in teaching practice were highlighted, such as the need for constant updating, as well as the planning of student engagement strategies. Regarding unlearning, this was identified as a phenomenon present in teaching practice, involving the redefinition of knowledge and the breaking of paradigms, in a continuous process of learning, unlearning, and relearning. In this perspective, the study proposes an integrative concept for unlearning, as well as an individual unlearning cycle, highlighting facilitating and hindering factors, as well as links between unlearning and teaching practice. It is therefore affirmed that the research advances in the field of knowledge and directs new research on unlearning, considering it a relevant and necessary phenomenon for individuals, groups, and organizations, with collaborative potential in the redefinition of knowledge and in the mitigation of resistance in times of transformations, contributing to studies on its relationship with teaching practice, especially in the context of Education in Administration.